THE TRANSLATION OF ARTICLES "A/AN" AND "THE" INTO INDONESIAN - Simanjuntak, Herlina Lindaria (UG Journal, 2014)
Many novice translators face the dificulties to translate articles "a/an" and "the". This research was conducted to answer the question: What are the translations of articles "a/an" and "the" into Indonesian? The aims of the research are to find out the translations of articles "a/an" and "the". The source of the data is "The 8th Habit" by Covey, Stephen R and its translation version "Kebiasaan Kedelapan" by Brata, Wandi S and Isa Zein. This research uses a qualitative method. In this case, the researcher collected, classfied, identified the data concerning with the translation of articles "a/an" and "the". Then, the researcher calculated the percentage of the categorizations of the translation of articles "a/an" and "the". The result of the research show that there are two categories of translating articles "a/an" and "the", namely "translated and untranslated". Article "a/an" is translated into seorang,  sebuah, semacam, sesuatu, seseorang, satu, sebagai, suatu, and the rest are  not translated. Article "the" is translated into nya, tersebut, itu, ini, kita, yang, di sana, di sini, di situ, sang, and untranslated.